Control of the HIV-1 Load Varies by Viral Subtype in a Large Cohort of African Adults With Incident HIV-1 Infection. (2nd April 2019) - Price, Matt A; Rida, Wasima; Kilembe, William; Karita, Etienne; Inambao, Mubiana; Ruzagira, Eugene; Kamali, Anatoli; Sanders, Eduard J; Anzala, Omu; Hunter, Eric; Allen, Susan; Edward, Vinodh A; et al.
Abstract: Few human immunodeficiency virus (HIV)–infected persons can maintain low viral levels without therapeutic intervention. We evaluate predictors of spontaneous control of the viral load (hereafter, "viral control") in a prospective cohort of African adults shortly after HIV infection. Viral control was defined as ≥2 consecutively measured viral loads (VLs) of ≤10 000 copies/mL after the estimated date of infection, followed by at least 4 subsequent measurements for which the VL in at least 75% was ≤10 000 copies/mL in the absence of ART. Multivariable logistic regression characterized predictors of viral control. Of 590 eligible volunteers, 107 (18.1%) experienced viral control, of whom 25 (4.2%) maintained a VL of 51–2000 copies/mL, and 5 (0.8%) sustained a VL of ≤50 copies/mL. The median ART-free follow-up time was 3.3 years (range, 0.3–9.7 years). Factors independently associated with control were HIV-1 subtype A (reference, subtype C; adjusted odds ratio [aOR], 2.1 [95% confidence interval CI, 1.3–3.5]), female sex (reference, male sex; aOR, 1.8 [95% CI, 1.1–2.8]), and having HLA class I variant allele B*57 (reference, not having this allele; aOR, 1.9 [95% CI, 1.0–3.6]) in a multivariable model that also controlled for age at the time of infection and baseline CD4 + T-cell count. We observed strong associations between infecting HIV-1 subtype, HLA type, and sex on viral control in this cohort. HIV-1 subtype is important to consider when testing and designing new therapeutic and prevention technologies, including vaccines. Abstract : Human immunodeficiency virus type 1 (HIV-1) subtype is important. We show that HIV subtype A is associated with viral control, using subtype C as a reference. Data from this and other studies suggest that HIV-1 subtype should be considered when designing new HIV therapeutic agents, prevention modalities, and vaccines.